Ensemble learning to generate virtual data for pattern recognition and its possibility of application to strategy inference in table tennis - Hayashi, I.; Irie, H. (IES 2019: Proceedings of the 23rd Asia Pacific Symposium on Intelligent and Evolutionary Systems, 2019)
Pattern recognition techniques are a class of method used to categorize observations across multiple classes. The structure and learning method of a model are selected so as to maximize the classification accuracy obtained over a certain data set. Methods also exist to improve accuracy by suitably structuring the training data [1]. Ensemble learning [2, 3, 4, 5] can be seen as one such method.